Poster 190: Epidemiology of Hamstring Tears in NCAA Sports: 2014/15-2018/19 - Boltz, A.; Wait, J.; Cheatham, S.; O`Connell, R.; Chandran, A.; Hooper, N. (Orthopaedic Journal of Sports Medicine, 2022)
Objectives: Hamstring tears are one of the most common muscular injuries seen in athletes [1]. These injuries are especially prevalent in sports associated with sprinting or jumping, with previous literature indicating that football, soccer, and track athletes are most at risk [1]. Hamstring injuries are classified into strains (Grade I), partial tears (Grades 2) and full thickness tears (Grade 3). Previous literature has described the epidemiology of hamstring strains/tears in NCAA athletes from 2009-2014 [1]. The aim of this study was to describe the epidemiology of hamstring tears in NCAA sports during 2014/15-2018/19. Methods: This study utilized NCAA Injury Surveillance Program (ISP) exposure and injury data submitted by athletic trainers (ATs) at participating institutions (via their respective Electronic Medical Records system) during the 2014/15-2018/19 academic years. Hamstring Tear (Partial or Complete) rates (stratified by sport, event type, and sex) per 10,000 athlete-exposures (AEs) and rate profile plots by event type stratified by sex were constructed. The distribution of injuries by history (new, recurrent) and timeloss (>1 day [TL]; non-timeloss [NTL]) was also examined. Injury Rate Ratios (IRRs) were constructed to evaluate differential injury rates by event type (practice, competition) and sex (male, female [for sex-comparable sports]) and injury proportion ratios (IPRs) were used to evaluate differential proportions by injury history (new, recurrent) and timeloss (TL, NTL); effect estimates with 95% CIs excluding 1.00 were considered statistically significant. Results: Across the study period, 2,096 hamstring tears from 8,474,400 AEs (2.47 per 10,000 AEs) were reported to the NCAA ISP. Amongst men`s sports, overall injury rates were highest in soccer (5.97 per 10,000 AEs), football (4.35 per 10,000 AEs), and track & field (3.57 per 10,000 AEs). In women`s sports, overall injury rates were highest in soccer (3.13 per 10,000 AEs), field hockey (2.09 per 10,000 AEs), and track & field (1.98 per 10,000 AEs). The rate of hamstring tear injuries in men`s/women`s competitions increased between 2014/15 and 2015/16, then decreased across the study period. Whereas the rate of hamstring tear injuries in men`s/women`s practice remained stable across the study period. Recurrent hamstring tears accounted for comparable proportions of all hamstring tears in men`s (14.8%) and women`s (11.5%) sports. A greater proportion of injuries in men`s sports (as compared with women`s sports) resulted in TL (IPR=1.33; 95% CI=1.21, 1.47). Among sex-comparable sports, injury rates were higher in the following men`s sports (as compared with respective women`s sports): baseball (IRR= 1.79; 95% CI=1.31, 2.44) [compared to women`s softball], soccer (IRR= 1.91; 95% CI=1.54, 2.37), and track & field (IRR= 1.80; 95% CI= 1.43, 2.27). Conclusions: Across all NCAA sports, hamstring strain incidence was highest in men`s soccer, men`s football, and men`s track & field. Hamstring tear incidence was higher among men`s baseball, soccer, and track & field compared to women`s comparable sports. Elucidating contributory factors that explain higher hamstring tear incidence in men`s sports (compared to sex-comparable women`s sports) warrants further attention. The development and improvement of hamstring tear injury prevention programs to reduce the burden of this injuries in all NCAA athletes remains critical. In evaluating the temporal patterns in hamstring tear incidence in NCAA sports by event type and stratified by gender, the competition-related injury rate in men`s and women`s sports followed a similar pattern and was lower in 2018/19 compared to 2014/15. A greater proportion of hamstring tears in Men`s sports resulted in time loss of >1 day as compared with hamstring tears in women`s sports. Compared to the previous study period (2009/10-2013/14), a higher proportion of all injuries in the present study were recurrent hamstring tears and a higher proportion of all injuries in this study resulted in time loss of >1 day. [1] In sum, this information can aid sports medicine professionals in identifying athletes who may be at risk for injury and may be valuable in counseling patients with regards to rehabilitative treatment timeline expectations. In order to decrease risk of hamstring tear incidence, sport and athlete specific preventative rehabilitation techniques isolating and targeting the hamstring muscles may be beneficial. Disclosures and funding sources: The NCAA Injury Surveillance Program was funded by the NCAA. The Datalys Center is an independent nonprofit organization that manages the operations of the NCAA ISP. The content of this report is solely the responsibility of the authors and does not necessarily represent the official views of the funding organization.We thank the many ATs who have volunteered their time and efforts to submit data to the NCAA ISP. Their efforts are greatly appreciated and have had a tremendously positive effect on the safety of high school and collegiate student-athletes.